Spring 1995 field report, Hank Zaletel - Zaletel, Hanket al (1995)
An annotated list of birds sighted by Hank Zaletel dated May 30, 1995. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1995. Epson - sheet feed/flatbed